Quantifying bacterial concentration in water and sand media during flow-through experiments using a non-invasive, real-time, and efficient method - Zhang, Xiaoming; Chen, Fengxian; Yang, Liqiong; Qin, Fucang; Zhuang, Jie (Frontiers in Microbiology, 2022)
Monitoring the dynamics of bacteria in porous media is of great significance to understand the bacterial transport and the interplay between bacteria and environmental factors. In this paper, we reported a noninvasive, real-time, and efficient method to quantify bioluminescent bacterial concentration in water and sand media during flow-through experiments. First, twenty-seven column experiments were conducted, and the bacterial transport was monitored using a real-time bioluminescent imaging system. Next, we quantified the bacterial concentration in water and sand media using two methods -viable count, and bioluminescent count. The principle of the bioluminescent count in sand media was, for a given bioluminescence image, the total number of bacteria was proportionally allocated to each segment according to its bioluminescence intensity. We then compared the bacterial concentration for the two methods and found a good linear correlation between bioluminescent count and viable count. Finally, the effect of porous media surface coating, pore water velocity and ionic strength on bioluminescent count in sand media were investigated, and the results showed that the bioluminescence counting accuracy was most affected by surface coating, followed by ionic strength, and was hardly affected by pore water velocity. Overall, the study proved that the bioluminescent count was a reliable method to quantify bacterial concentration in water (106 to 2×108 cell mL-1) or sand media (5×106 5×108 cell cm-3). This approach also offers a new way of thinking for in-situ bacterial enumeration in two-dimensional devices such as 2D flow cell, microfluidic device, and rhizobox.